2019
DOI: 10.1210/jc.2019-00235
|View full text |Cite
|
Sign up to set email alerts
|

Synonymous but Not Silent: A Synonymous VHL Variant in Exon 2 Confers Susceptibility to Familial Pheochromocytoma and von Hippel-Lindau Disease

Abstract: Context von Hippel-Lindau (VHL) disease, comprising renal cancer, hemangioblastoma, and/or pheochromocytoma (PHEO), is caused by missense or truncating variants of the VHL tumor-suppressor gene, which is involved in degradation of hypoxia-inducible factors (HIFs). However, the role of synonymous VHL variants in the disease is unclear. Objective We evaluated a synonymous VHL variant in patients with familial PHEO or VHL diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Using the fibroblasts derived from three patients and two healthy individuals, we confirmed that the c.414A > G mutation led to VHL exon 2 skipping and generated less E1E2E3 but more E1E3, consistent with previous reports [17,18]. Mechanistically, c.414A > G mutation may dysregulate the exonic splicing enhancer in exon 2 and cause exon 2 skipping [17].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Using the fibroblasts derived from three patients and two healthy individuals, we confirmed that the c.414A > G mutation led to VHL exon 2 skipping and generated less E1E2E3 but more E1E3, consistent with previous reports [17,18]. Mechanistically, c.414A > G mutation may dysregulate the exonic splicing enhancer in exon 2 and cause exon 2 skipping [17].…”
Section: Discussionsupporting
confidence: 87%
“…The findings from this study and others [17,18], strongly advocate changing the status of VHL c.414A > G variant from "Uncertain significance" to "Pathogenic" for VHL disease in human variant databases (e.g. Clin-Var).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations